1989
DOI: 10.1093/rheumatology/28.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Outcome From Multiple Joint Replacement Surgery to the Lower Limbs

Abstract: All patients who had three or more major joints (hips or knees) replaced were identified from operation records at one hospital and reviewed to assess outcome. Forty-three were found to suffer from rheumatoid arthritis, four from osteoarthritis and three from psoriatic arthritis. Eight patients had died an average of 2.6 years (range 1-7 years) after their last operation and this was higher than expected, even for RA. Average follow-up in the 36 surviving RA sufferers was 1.8 years, with a minimum of 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Total hip (THA) and total knee (TKA) arthroplasties have been accepted as a standard treatment for joint destruction in patients with rheumatoid arthritis (RA) [1][2][3][4][5][6]. Patients with progressive RA frequently undergo multiple arthroplasties in the lower extremities.…”
Section: Introductionmentioning
confidence: 99%
“…Total hip (THA) and total knee (TKA) arthroplasties have been accepted as a standard treatment for joint destruction in patients with rheumatoid arthritis (RA) [1][2][3][4][5][6]. Patients with progressive RA frequently undergo multiple arthroplasties in the lower extremities.…”
Section: Introductionmentioning
confidence: 99%
“…McDonald [11], McElwain and Sheehan [12], and Marks [9] showed no improvement in knee flexion and Johnson [5] and Yoshino et al [16] reported a reduction in flexion. Walker et al [15] reported an improvement of 8°and Hoekstra et al [3] an improvement of 26°but this was in patients whose average pre-operative flexion was only 54°. Our results are similar to Hoekstra's and better than other author's, both in pain relief and function, with a longer follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…Marks [9] reported that only 59% of 21 rheumatoid patients with multiple replacements were pain-free. Walker et al [15] in a series of 36 patients with 3 or more joints replaced and a mean follow-up of 20 months recorded that 49% of patients had only moderate or slight improvement of pain and McDonagh et al [10] reported further on this group indicating that 7 knees required revision after a mean of 3 years. Hoekstra et al [3] reported on 14 rheumatoid patients with 4 joint replacements and a mean follow-up of 71 months with pain relief in all patients and no loosening.…”
Section: Discussionmentioning
confidence: 99%
“…There is very little literature on the relationships of disabilities to each other and their social consequences. Most of the work using the HAQ and other validated instruments report only on the overall scores (23)(24)(25). While this is appropriate for formal studies of outcome, we would suggest that more attention needs to be paid to the differential impact of different disabilities in exploratory studies or secondary analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While this is appropriate for formal studies of outcome, we would suggest that more attention needs to be paid to the differential impact of different disabilities in exploratory studies or secondary analysis. Such research could increase our understanding of the factors affecting social outcome (handicap) and hence, quality of life (18,19,25).…”
Section: Discussionmentioning
confidence: 99%